Improving climate risk management at local level techniques, case studies, good practices and guidelines for World Meteorological Organization members - Martínez, R.; Hemming D; Malone L; Bermudez, N.; Cockfield G; Diongue, A.; Hansen, James; Hildebrand A; Ingram, K.; Jakeman G; Kadi Kadi, Hame A.; McGregor GR; et al. (IntechOpen, 2012)
Climate can be viewed in a number of ways. As a constraint or setting, climate provides the broad boundary conditions within which a range of ecosystems services function. Climate may be considered a determinant in that it may be part of a causal chain of direct or indirect events leading to a particular impact or outcome. Climate can also be viewed as a resource; this notion implies that climate has a value, could be managed and manipulated and by extension could be allocated. More often than not, climate is viewed as a hazard. Whichever of these views of climate is adopted, it is clear that climate has a close relationship with nature and society and therefore climate variability and change may pose a range of risks for environments, societies and economies.